Pengaruh Dukungan Sosial dan Spiritualitas Terhadap Resiliensi Remaja Dengan Orang Tua Tunggal - Ramadan, Mohamad Fajar (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The increasing prevalence of adolescents raised by single parents has raised concerns regarding their psychological adjustment and capacity to cope with life challenges. Adolescents growing up in single-parent families often face various social, emotional, and economic stressors, making resilience a crucial psychological resource for their development. This study aimed to examine the effects of social support and spirituality on the resilience of adolescents raised by single parents. A quantitative approach was employed using a correlational design. Convenience sampling was used to select 272 adolescent respondents aged 15 to 19 years who were raised by a single parent and resided in Karawang Regency. Data were collected using the Multidimensional Scale of Perceived Social Support (MSPSS), the Spiritual Health Scale, and the Resilience Adaptation Scale developed by Amaliyah and Fauziah. Multiple regression analysis was applied to examine the effects of the independent variables on adolescent resilience. The results indicated that social support and spirituality had positive and significant effects on resilience, both partially and simultaneously. Together, these variables accounted for 33.7% of the variance in adolescent resilience, while the remaining 66.3% was explained by other factors not examined in this study. These findings suggest that adolescents who perceive higher levels of social support and possess stronger spiritual well-being tend to demonstrate greater resilience in facing life challenges. The results reinforce the importance of strengthening social support networks and fostering spiritual development as protective factors for adolescents raised by single parents. This study provides important implications for guidance and counseling services, educators, and family support programs in promoting resilience among adolescents from single-parent families.